2016
DOI: 10.1097/jcn.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of mHealth-Based Heart Failure Interventions

Abstract: Background The popularity of mobile phones and similar mobile devices makes it an ideal medium for delivering interventions. This is especially true with heart failure (HF) interventions, in which mHealth-based HF interventions are rapidly replacing their telephone-based predecessors. Purpose This systematic review examined the impact of mHealth-based HF management interventions on HF outcomes. The specific aims of the systematic review are to: (1) describe current mHealth-based HF interventions and (2) disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 27 publications
1
110
1
9
Order By: Relevance
“…28,30,3335 Our findings are consistent with other reviews that reported overall positive potential for mHealth technology to improve various behaviors and clinical outcomes in different populations. 17,4650 Compared to others, our paper provided an updated search of focused text messaging and mobile apps interventions with clinical outcomes related to the secondary prevention of CVD. In addition, our study confirms that despite the study population of CVD patients being older, a strong majority of the studies had positive clinical outcomes and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…28,30,3335 Our findings are consistent with other reviews that reported overall positive potential for mHealth technology to improve various behaviors and clinical outcomes in different populations. 17,4650 Compared to others, our paper provided an updated search of focused text messaging and mobile apps interventions with clinical outcomes related to the secondary prevention of CVD. In addition, our study confirms that despite the study population of CVD patients being older, a strong majority of the studies had positive clinical outcomes and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In HF studies, mHealth-based interventions have used mobile devices as part of a larger monitoring system, usually in conjunction with a blood pressure measuring device and a weighing scale. 57 Mobile devices have also been used to deliver HF-related educational messages. 8,9 mHealth-based interventions have been associated with improved HF self-management, 8,9 improved quality of life, 8,10 and lower mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Over the decade, they have shared the same goal, worked mostly with the same set of basic vital signs and physiological parameters, however there is still a lot more to be covered to create the perfect system 8 . The ability to detect and alert patients about ailments would result in a decrease in sudden death and outbreaks experienced around the globe, both in developing and developed nations where medical care is either too expensive or inaccessible at patients' current location 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 provides a tabular summary of our findings for telemedical health care services as related to cardiovascular health and wearable devices in recent times. Other such review out of our year of study could be found in some of the works referenced [8][9][10]16 . No autonomous SOS algorithm only during excess precipitation (cold sweat) and manual button press, No additional functionality.…”
Section: Resultsmentioning
confidence: 99%